FEARURES OF THE ORGANIZATION OF CEPHALOPODS. - RENU ANAND (International Journal of Multidisciplinary Research and Studies, 2020)
Cephalopods are a fascinating group of marine animals that exhibit a range of unique features that allow them to thrive in their environment. From their advanced nervous system and specialized arms and tentacles to their ability to change color and texture and their diverse diet, cephalopods have captured the attention of scientists and the public alike. This paper provides an overview of the organization of cephalopods, highlighting 20 key features that make them such remarkable creatures. These features include their advanced vision, jet propulsion, ink defense, sensory organs, adaptability, shell, regeneration, metabolism, social behavior, diverse diet, habitat, communication, memory, size, and lifespan.Cephalopods are a class of marine animals that include octopuses, squids, cuttlefish, and nautiluses. They are characterized by their unique morphology, including a distinct head, a set of arms or tentacles, and a mantle or body. Cephalopods are known for their impressive cognitive abilities and complex behaviors, which are facilitated by their advanced nervous system and unique organization.